The Influence of Information Services on Students' Learning Concentration - Munthe, Sarmila Yanti; Hasibuan, Ali Daud (Tarbiyah Wa Ta'lim: Jurnal Penelitian Pendidikan dan Pembelajaran, 2024)
This study aims to determine the influence of information services on the learning concentration of students at SMP IT Al-Hijrah Laut Dendang. The research method used is a quasi-experimental design with a one-group pretest-posttest format. The sample consists of 38 students from SMP IT Al-Hijrah, selected through purposive sampling. Data collection was conducted using a questionnaire on learning concentration designed with a Likert Scale, developed and modified based on various existing theories. The data analysis technique employed is the paired sample t-test. The results of the study show that the average pretest score of students is 52.05, while the posttest score is 83.68. The paired sample t-test conducted using SPSS 23 yielded a significance value of 0.001. According to the decision rule in the paired sample t-test, where a significance value < 0.05 indicates significance, the result of 0.001 < 0.05 leads to the acceptance of H1 and rejection of H0. It can be concluded that there is a significant influence of information services on the learning concentration of 7th-grade students in the Ikhwan class at SMP IT Al-Hijrah Laut Dendang for the academic year 2023/2024.